Ghosts of Greenglass House - Milford, Kate (Houghton Mifflin Harcourt, 2018)
Milo usually finds winter vacation relieving, but this year there is no snow, and a teacher has been giving him a tough time at school by not realizing he hates attention, and on top of it all there is a lone, mysterious guest staying at his family's inn who is determined to sketch every stained-glass window in the place. Worst of all, Milo's friend Meddy seems absent--but then the bell rings.